Quantitative Estimation of Annual Soil Loss by Integration of Remote Sensing, GIS, and Universal Soil Loss Equation (Case Study: Tartus District, Syria) - Al-Abed, Mohammad; Salhab, Jalal; Ebrahim, Hani; Dweri, Safa (Annals of Arid Zone, 2019)
This paper describes the procedures employed to integrate Remote Sensing (RS) and Geographic Information System (GIS) techniques in an effort to characterize the spatial distribution of the risk of soil erosion by water on lands of Tartus district, Syria. The universal soil loss equation (USLE) is used to calculate the annual soil loss rates for Tartus soils. Mainly Landsat Enhanced Thematic Mapper (ETM) dated 5/2009, thematic maps such as land capabilities, landuse, digital elevation model (DEM) and climate data were used to determine USLE factors. Integration of these data sets resulted in a map of polygons with unique combinations of USLE factor values. The study showed that water erosion mainly threatens those soils on hilly lands where vegetation is sparse or absent and exposed to heavy rainfall. Mostly these lands extend around these towns and villages of Tiro, Jwibat, Hrison, Shiekh Bader, HamamWasel, Dulbeh and Safasif, where these soil loss was about 150 t h-1 y-1 which account for 0.13% of the soil loss. These quantities of annual soil loss can be considered as a very severe amounts, and if this water erosion persists at these high rates, the soil will be eroded and the parent material will be exposed in these regions. The study also mentioned a package of remedial measures so as to combat land degradation in the study area. Key words: Water erosion, USLE, Landsat ETM, GIS, Sustainable land use, Tartus.